Penerapan Model Pembelajaran Cooperative Script Untuk Meningkatkan Keterampilan Menyimak Murid Kelas II SDN 25 Koto Panjang Kota Padang - Iffa Rahnurmi Mudri; Vini Wela Septiana (PT Suria Academic Press, 2026)
This research is motivated by the low listening skills of students in Indonesian language subjects. The purpose of this study is to determine the improvement of students' listening skills in Indonesian language learning through the application of the Cooperative Script model. This type of research is classroom action research (CAR). This research improves and enhances the quality of the learning process and outcomes. The subjects of the study were 28 second-grade students of SDN 25 Koto Panjang, Padang City, researchers as practitioners, 2 observers. This research was conducted in two cycles, each cycle consisting of two meetings. The results of the study showed that students' listening skills increased in each cycle. Seen from the assessment of the Module cycle I with an average value of 82% (B) cycle II with a value of 95% (A). The results of observations of the teacher aspect of cycle I with an average value of 87% (SB), cycle II with an average value of 95% (SB). The results of observations of the student aspect of cycle I with an average value of 82% (B), cycle II with an average value of 92% (SB). The results of listening skills in cycle 1 with an average pre-listening score of 76%, while listening 77%, after listening 75%, cycle II with an average pre-listening score of 82%, while listening 81%, after listening 82%. So it can be concluded that the Cooperative Script learning model can improve the listening skills of second-grade students at SDN 25 Koto Panjang, Padang City.